2008
DOI: 10.1007/s10494-008-9165-z
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Investigation of the Time Scales of Single Droplet Burning

Abstract: The effect of gas phase velocity fluctuations on single droplet burning is investigated numerically. The main objective of this study is to understand the effect of gas phase turbulence on nitric oxide formation in single droplet flames. Since the interaction of gas phase velocity fluctuations with droplet burning is of sequential character, a separate investigation of droplet momentum coupling and droplet burning is performed. Momentum coupling controls droplet relaxation against changes of the gas phase velo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 30 publications
1
2
0
Order By: Relevance
“…Cho et al [16], in a numerical study, reported that turbulence intensity of a free airstream has a marginal effect on the burning rate of a stationary droplet under elevated ambient conditions (2.02T c and 0.47P c where T c and P c are the fuel critical temperature and pressure, respectively). Similar conclusion was also reported by Beck et al [17], who investigated numerically the effect of turbulence intensity on a moving burning droplet in a hot (0.88T c and 1.43T c ) airstream at atmospheric pressure.…”
Section: Introductionsupporting
confidence: 87%
See 1 more Smart Citation
“…Cho et al [16], in a numerical study, reported that turbulence intensity of a free airstream has a marginal effect on the burning rate of a stationary droplet under elevated ambient conditions (2.02T c and 0.47P c where T c and P c are the fuel critical temperature and pressure, respectively). Similar conclusion was also reported by Beck et al [17], who investigated numerically the effect of turbulence intensity on a moving burning droplet in a hot (0.88T c and 1.43T c ) airstream at atmospheric pressure.…”
Section: Introductionsupporting
confidence: 87%
“…The effect of forced flow/convection on hydrocarbon droplet combustion has been studied quite extensively under laminar flow conditions and therefore there is a wealth of knowledge (see, e.g., recent references [1][2][3][4][5][6][7][8][9][10], and references cited therein, M. Birouk ( ) 路 S. L. Toth Department of Mechanical Engineering, University of Manitoba, Winnipeg, MB R3T 5V6, Canada e-mail: madjid.birouk@umanitoba.ca to cite only a few). However, studies reporting on the effect of a turbulent or an acoustic field are quite limited (e.g., [11][12][13][14][15][16][17]). Birouk et al [11] investigated experimentally the combustion of a suspended hydrocarbon droplet under turbulent flow environment at atmospheric/room conditions.…”
Section: Introductionmentioning
confidence: 99%
“…They concluded that the mixing of the droplets, and so the evaporation, has an impact on the burning rate and this is related to combustion instabilities. An extensive numerical analysis has been performed by Beck, Koch, and Bauer [8] on the effects of slip velocity fluctuations on a single burning droplet. NO formation was predicted to vary with the forcing frequency, depending on changes in the droplet-to-flame distance.…”
Section: Introductionmentioning
confidence: 99%